Phlorofucofuroeckol-A, a Potent Inhibitor of Aldo-keto Reductase Family 1 Member B10, from the Edible Brown Alga Eisenia bicyclis - Lee, Joo Young; Kim, Sang Min; Jung, Woo-Suk; Song, Dae-Geun; Um, Byung-Hun; Son, Jin-Ki; Pan, Cheol-Ho (KOREAN SOC APPLIED BIOLOGICAL CHEMISTRY, 2012)
Aldo-keto reductase family 1 member B10 (AKR1B10) belongs to a superfamily of NADPH-dependent aldo-keto reductases and is considered a biomarker of several cancers. Inhibition of recombinant human AKR1B10 (rhAKR1B10) was assayed using 31 seaweed extracts, among which, an Eisenia bicyclis extract was selected for further study. To identify the compounds in E. bicyclis responsible for inhibitory effects on rhAKR1B10, five compounds were isolated by bioactivity-guided fractionation and isolation. Among them, phlorofucofuroeckol-A (PFF-A), isolated from an ethyl acetate fraction, exhibited the greatest inhibition of rhAKR1B10. The inhibitory rate of PFF-A against rhAKR1B10 was 61.41% at 10 mu M, with an IC50 of 6.22 mu M. Enzyme kinetic analyses revealed non-competitive inhibition with a K-D of 2.76 mu M. These results indicate that PFF-A from E. bicyclis may be a promising anticancer agent.
Keywords: ECKLONIA-KUROME; PHLOROTANNINS; AKR1B10; IDENTIFICATION; PURIFICATION; METABOLISM; MARKER; TARGET; 1B10